Acute influence of resistance exercise on basketball shooting mechanics and accuracy - Cabarkapa, Dimitrije; Cabarkapa, Damjana V.; Ciccone, Anthony B.; Whiting, Shay M.; Philipp, Nicolas M.; Eserhaut, Drake A.; Fry, Andrew C. (Frontiers in Sports and Active Living, 2023)
The purpose of the present study was to examine the acute impact of resistance exercise on basketball shooting mechanics and accuracy. Ten resistance-trained recreationally active men with previous basketball playing experience (x̄ ± SD; height = 182.6 ± 9.7 cm; body mass = 79.2 ± 13.9 kg; age = 25.6 ± 5.5 years) performed control, upper-body, and lower-body training sessions in randomized order followed by 5 sets of stationary free-throw (4.57 m), two-point (5.18 m) and three-point (6.75 m) basketball shooting drills in 30 min time increments. Each testing session was separated 3–7 days apart. Kinematic variables during both the preparatory and release phases of the shooting motion were derived from a high-definition camera recording at 120 fps positioned 10 m away perpendicular to the participant's shooting plane of motion. Restricted maximum likelihood linear mixed-effects model analysis revealed that a combination of all fixed effects could account for <1% of the total variance in each dependent variable pertaining to basketball shooting mechanics. A 9.9–11.8% decrease in two-point and three-point shooting accuracy was observed immediately following an upper-body training session. However, the observed performance suppression disappeared 30 min post-exercise completion. Overall, the findings suggest that performing upper-body or lower-body resistance training prior to on-court practice sessions has no impact on free-throw, two-point, and three-point biomechanical parameters examined in the present study and a minor acute impact on mid-range and long-range shooting accuracy in male basketball players.